Composite adaptive attitude control for combined spacecraft with inertia uncertainties - Xu, Yiqi; Hu, Qinglei; Shao, Xiaodong (Aerospace science and technology, 2022)
This paper examines the attitude control problem of the combined spacecraft subject to inertia uncertainties. A composite adaptive finite-time control scheme with guaranteed parameter convergence is proposed to address this challenging problem, in the absence of persistent excitation. As a stepping stone, the attitude dynamics of the combined spacecraft is first established with explicit consideration of the center-of-mass variation and thruster reconfiguration. Then, a composite adaptive finite-time controller is developed based on a constructive time-varying sliding manifold, and in particular, the concurrent learning technique is used in conjunction with the dynamic regressor extension and mixing procedure to achieve parameter convergence under finite excitation that is strictly weaker than the persistent excitation. Lyapunov stability analysis shows that the derived adaptive controller can simultaneously guarantee finite-time convergence of the attitude tracking and parameter estimation errors; moreover, its robustness against inertia variations and external disturbances is also analyzed. Finally, a set of numerical simulations under ideal and practical scenarios are performed to validate the effectiveness and outperformance of the proposed method.